Using Serious Game in Public Schools for Training Fire Evacuation Procedures - Paulo Victor Rodrigues de Carvalho; Darcio Otaviano Ranauro; Antonio Carlos de Abreu Mol; Alessandro Jatoba; Ana Paula Legey de Siqueira (Serious Games Society, 2022)
Most Brazilian schools do not offer evacuation training from their buildings in the event of a fire. The lack of safety culture among students and teachers, coupled with a lack of knowledge and training on safety protocols to follow when facing fires, have led to unwanted outcomes, including unnecessary injuries and even death. This study describes the development of a prototype of a Serious Game to teach fire evacuation procedures in schools in the case of fire, aiming to help students to learn fire safety procedures, to know how to behave in case of fire, and to start discussions to create a positive fire safety culture. The prototype was used and evaluated by 35 public school students from 12 to 16 years old. The results indicated that students' knowledge on how to behave in case of fire after they played the game was significantly improved, and the discussions triggered by the game contributed to the creation of a positive fire safety culture in school. The game developed proved useful to teach evacuation procedures and is available for use by all public schools in the city.